PENGARUH STRUKTUR JATUH TEMPO HUTANG TERHADAP MANAJEMEN LABA (Studi Empiris Perusahaan Manufaktur yang Terdapat di Bursa Efek Indonesia Tahun 2019-2021) - Putri, Rusita Aprilla; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2024)
This research aims to examine the influence of debt maturity structure on earnings management strategies. This research focuses on debt maturity reports in manufacturing companies which influence accrual earnings management and real earnings management in the period 2019 to 2021.The sampling method used in this research is purposive sampling, where the number of samples in this research is 105 issuers. This research uses multiple linear regression analysis methods and classical assumption tests.The results of the research show that long-term debt and short-term debt have a positive and significant effect on accrual earnings management in manufacturing companies listed on the IDX for the 2019-2021 period, then long-term debt and short-term debt have a positive and significant effect on the company's real earnings management manufacturers listed on the IDX for the 2019-2021 period. Issuers must clearly disclose the company's use of accruals and the reasons behind them in financial reports and reports. Transparency is very important to maintain investor and stakeholder trust.